Features of using artificial intelligence technologies in the self-education activities of academic and pedagogical staff in higher education institutions - Samko Alla (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The article is devoted to the problem of using artificial intelligence in the self-educational activities of research and teaching staff of higher education institutions. The relevance of the research topic is emphasized, which is due to the need to improve the quality and effectiveness of the introduction of open science tools and services into self-education activities, increase the efficiency of their use in the national science and education system, and improve the level of training of educational specialists, in particular, research and teaching staff of higher education institutions. The purpose of the study is to carry out a theoretical analysis of the significance of artificial intelligence in the process of self-education of scientific and pedagogical staff of higher education institutions. In order to achieve the goal and implement the tasks, a set of theoretical research methods was used: comparative and systematic analysis of scientific sources on information technology; analysis of existing approaches to the use of artificial intelligence in education; assessment of their efficiency and effectiveness; systematization, verification, interpretation, synthesis and generalization of the results. The article highlights the available artificial intelligence services that can be used for self-education purposes. The possibilities of using cloud resources and services for the implementation of self-educational activities of scientific and pedagogical staff of higher education institutions are analyzed. It is concluded that artificial intelligence is an integral part of the digital transformation of education, a powerful auxiliary tool in the implementation of self-education activities of research and teaching staff of higher education institutions. It has been determined that the use of cloud-based platforms’ tools and services provides open access to relevant research results; implementation of own research projects; establishment of international cooperation and exchange of experience; improvement of the overall quality of research and educational services.